Perception of reality in the Asia Pacific region: The cases of India, Bangladesh, Pakistan, and Indonesia - Díez Medrano, Javier (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The subject “Perception of reality from the eyes of the population of Asia Pacific” highlights how the inhabitants of India, Bangladesh, Pakistan, and Indonesia access information, as well as the sociodemographic factors that influence the choice of media instead of others. The World Values Survey and the Statistical Research Department of Statista confirm that religion, age, and freedom of access to social networks are the key variables to explain their way of accessing information and perceiving their reality.